Relationship between Psychosocial Factors and Glycemic Control in 7-16 Years Old Children with Type 1 Diabetes - Firoozeh Derakhshanpour; Sakineh Mohammadian; Hosein Zaeri2; Yalda Sanei; Kashani Leila (Golestan University Of Medical Sciences, 2020)
Background and objectives: Diabetes mellitus is a metabolic disease characterized by hyperglycemia due to defects in insulin secretion or action. One of the consequences of diabetes is depression, which itself is related to complication of diabetes. Given the lack of enough studies on the relationship between psychological variables of parents and level of HbA1C in children with type 1 diabetes in Iran, we examined the relationship between psychosocial factors and glycemic control in children aged 7-16 years with type 1 diabetes. Methods: This is a cross-sectional study conducted on all children with type 1 diabetes who were referred to Taleghani childrenchr('39')s hospital in Gorgan, Iran. Data were collected using the General Health Questionnaire, the Strengths and Difficulties Questionnaire and a parenting style questionnaire. The collected data were analyzed in SPSS software (version 17). Results: Overall, 64 diabetic children aged 7 -16 years who had a record file at the hospital were enrolled in the study. Children of homemakers and highly educated mothers had better glycemic control. In addition, the General Health Questionnaire test score of mothers had an inverse relationship with glycemic control in children with type 1 diabetes. Moreover, daring parenting style seemed to have a more positive impact on glycemic control of diabetic children compared to permissive and authoritarian parenting styles. Conclusion: Our findings demonstrate that various parental variables may affect glycemic control in children with type 1 diabetes. Children with poor glycemic control have more personality and psychosocial problems. We suggest endocrinologists to refer children with type 1 diabetes and their parents to psychiatrists for psychological assessment and psychoeducation.